Trends in oral antimicrobial drug prescriptions in the outpatient setting. - Bhimsan, Nireshini (My University, 2014)
All prescriptions dispensed in the managed care environment for the period 01 May 1998 to 31 May 1998 were evaluated to identify oral antimicrobial drugs contained in these prescriptions. A total of 2711 prescriptions were evaluated, with 788 antimicrobial prescriptions being identified. The oral antimicrobial prescribing frequency in the managed care environment for May 1998 was 29.07%. In the United States, these drugs represent 12-14% of all drugs prescribed by office based physicians. Thus the prescribing frequency for managed care is high and could be attributed to the high antimicrobial prescribing frequency for the common cold and influenza during this period. Oral antimicrobial drugs identified were classified into 8 different drug classes, with the penicillins being prescribed most frequently, accounting for 35.41% of all antimicrobial prescriptions. Amoxycillin was the most frequently prescribed active ingredient within the penicillin drug class. Antimicrobial drugs were most frequently prescribed for respiratory disorders and symptoms, which accounted for 65.68% of all diagnoses. The managed care data showed a variation in trends of antimicrobial drug use in specified medical diagnoses compared to the Essential Drug List (EDI.) recommendations for South Africa. Antimicrobial drugs are frequently used in viral conditions like the common cold and influenza; acute, upper respiratory infections and acute pharyngitis, where clearly, these drugs have no role. In addition, the trend in managed care is towards the use of the newer, broader spectrum, more expensive antimicrobial agents compared to the EDL recommendations. Thus,this study indicates that clinical protocols and treatment guidelines are urgently required in managed care to ensure safe and effective antimicrobial use and to decrease problems of antimicrobial resistance, "his study indicated that the average antimicrobial prescription costs in managed care are higher than the cost calculated based on the EDL recommendations for antimicrobial prescribing in specified diagnoses. Significant cost savings could be achieved with the mplementation of the EDL guidelines.This study helped to assess the current practice of antimicrobial use in the managed care environment and assists in the development of future clinical guidelines and protocols to optimise antimicrobial utilisation and decrease costs associated with antimicrobial prescribing.